2014
DOI: 10.4331/wjbc.v5.i3.346
|View full text |Cite
|
Sign up to set email alerts
|

FoxO3a and disease progression

Abstract: highlighted as a critical protein that regulates numerous cell functions from proliferation/apoptosis to stressresistance and aging. FoxO3a has been found to be deregulated in several diseases and FoxO3a targeting approaches are currently underway to treat various types of cancers. This review will describe the current concept of FoxO3a's pathological role in various diseases and elucidate the regulatory mechanisms involved. It will also provide the clinical significance and strategies to target FoxO3a to limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 86 publications
1
113
0
3
Order By: Relevance
“…More importantly, FOXO3a has been found to increase several target genes, such as TRAIL, PUMA, FasL, and BIM, which is essential for the gefitinib-induced killing of NSCLC cells (14,27), and the suppression of FOXO3a in breast cancer cells result in a reduction of gefitinib-induced cell cycle arrest and cell death (18). These results are consistent with our observations, which showed that 24% of lung cancer patients with high FOXO3a have a better response to EGFR-TKIs and progression-free survival outcomes, suggesting that FOXO3a expression is involved in the regulation of the EGFR-TKI-induced apoptotic response and is a good marker for predicting the therapeutic effects of EGFR-TKIs in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, FOXO3a has been found to increase several target genes, such as TRAIL, PUMA, FasL, and BIM, which is essential for the gefitinib-induced killing of NSCLC cells (14,27), and the suppression of FOXO3a in breast cancer cells result in a reduction of gefitinib-induced cell cycle arrest and cell death (18). These results are consistent with our observations, which showed that 24% of lung cancer patients with high FOXO3a have a better response to EGFR-TKIs and progression-free survival outcomes, suggesting that FOXO3a expression is involved in the regulation of the EGFR-TKI-induced apoptotic response and is a good marker for predicting the therapeutic effects of EGFR-TKIs in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FOXO3a is a transcription factor that acts as a tumor suppressor by inducing cell cycle arrest, and the down-regulation of FOXO3a is involved in the tumorigenesis of various cancer types (14). Studies indicate that FOXO3a activity is negatively regulated by oncogenic kinases, such as AKT, IKK, and ERK (15)(16)(17), and the activation of these oncogenic kinases is associated with FOXO3a suppression, which triggers cancer progression.…”
Section: Nf-κb-driven Suppression Of Foxo3a Contributes To Egfr Mutatmentioning
confidence: 99%
“…In this study, we identified several miRNAs that are highly relevant to IRI and found that miR-155 expression was remarkably increased both in HK2 cells (a human renal tubular cell line) subjected to HRI and in renal tissues from IRI rats. FoxO3a is involved in the inhibition of cell death and the promotion of cellular growth in ischemic renal diseases [53]. Several miRNA databases, including TargetScan, miRDB and miRanda, show that FoxO3a is a potential target gene for miR-155.…”
Section: Mir-155 Directly Targets Foxo3a In Hk2 Cells During Hrimentioning
confidence: 99%
“…Autophagy is involved in tissue remodelling during embryonic development [7]. Involvement of autophagy in the liver fibrosis and other liver diseases is a well-established fact [4,8,9]. However, there is no direct link for miRNA-21 involvement in development of liver fibrosis [10,11].…”
Section: Mini Reviewmentioning
confidence: 99%